Direct growth of layered intercalation compounds via single step one-pot in situ synthesis1. Issue 57 (21st July 2015) - Yu, Jingfang; Xiang, Lichen; Martin, Benjamin R.; Clearfield, Abraham; Sun, Luyi
<x xml:space="preserve">Abstract</x> A single step one-pot in situ synthesis method was developed to directly grow layered intercalation compounds. This methodology is expected to be applicable to a wide range of layered materials.